Increase in potato yield by the combined application of biochar and organic fertilizer: key role of rhizosphere microbial diversity - Hou, Jianwei; Xing, CunFang; Zhang, Jun; Wang, Zuhua; Liu, Min; Duan, Yu; Zhao, Hui (Frontiers in Plant Science, 2024)
Purpose The large-scale planting of potatoes leads to soil degradation, thus limiting the potato yield. An effective method of improving soil quality involves the combined application of biochar and organic fertilizer. However, the proportion of biochar and organic fertilizer at which potato yield can be improved, as well as the improvement mechanism, remain unclear. Methods A combined application experiment involving biochar (B) and organic fertilizer (O) with four concentration gradients was conducted using the equal carbon ratio method. On this basis, rhizosphere soil fertility, bacterial community composition, and bacterial diversity in potato crops, as well as the potato yield difference under different combined application ratios, were investigated. Then, the direct and indirect effects of these factors on potato yield were analyzed. Results The results suggest that soil fertility was improved by the combined application of biochar and organic fertilizer, with the best effect being achieved at a ratio of B:O=1:2. The dominant bacterial communities in the potato rhizosphere included Proteobacteria, Actinobacteria, Gemmatimonadetes, Chloroflexi, and Bacteroidetes. When compared to the control, the relative abundance and diversity index of soil bacteria were significantly improved by the treatment at B:O=1:2, which exerted a stronger effect on improving the relative abundance of beneficial bacteria. Soil available phosphorus (AP), soil pH (SpH), and soil organic carbon (SOC) explained 47.52% of the variation in bacterial composition. Among them, the main factor was the content of soil available nutrients, while SpH generated the weakest effect. The bacterial diversity index showed a significant positive correlation with soil AP, SOC, available potassium (AK), total nitrogen (TN), and C/N ratio, and a significant negative correlation with SpH. Bacterial diversity directly affected the potato yield, while soil fertility indirectly affected potato yield by influencing the soil bacterial diversity. Conclusion The combined application of biochar and organic fertilizer elevates potato yield mainly by improving the diversity of bacterial communities in potato rhizosphere soil, especially the combined application of biochar and organic fertilizer at a 1:2 ratio (biochar 0.66 t ha-1+organic fertilizer 4.46 t ha-1), which made the largest contribution to increasing potato yield.